(untitled) (European Bison Conservation Newsletter, 2012)
The paper summarises results of the survey which goal was the evaluation of potential sites for the reintroduction of wisents to Western Rodopes, Bulgaria. Evaluated were there regions: Madzharovo, Byala Reka and Mursalica. First two were disqualified mostly because unfavorable habitat conditions (poor food base and limited water resources). In Mursalica region small population of wisents (up to 20 animals) could be maintained, providing there would be introduced and adequate protection against poaching and measures to prevent possible transmission of diseases from local livestock. The survey was performed under the framework of European Bison Friends Society.